The Role of Teachers in Increasing Students' Learning Motivation in Islamic Religious Education - Muh Ibnu Sholeh; Muhammad Haris; Nur ‘Azah; Mochammad Syafiuddin Shobirin; Sahri; Bambang Wahruddin; Hawwin Muzakki; Taufik Ismail; Himad Ali (Jurnal Pendidikan Agama Islam)
Purpose - This study examines teachers' roles in enhancing students' learning motivation in Islamic Religious Education (PAI) at MAN 2 Tulungagung. It explores teaching strategies, challenges faced, and supporting factors contributing to increased motivation.